2021
DOI: 10.3389/fmicb.2021.800125
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of Genes Involved in Sesquiterpene Alkaloid Biosynthesis in Trichoderma longibrachiatum MD33 and UN32

Abstract: Trichoderma longibrachiatum MD33, a sesquiterpene alkaloid-producing endophyte isolated from Dendrobium nobile, shows potential medical and industrial applications. To understand the molecular mechanisms of sesquiterpene alkaloids production, a comparative transcriptome analysis was performed on strain MD33 and its positive mutant UN32, which was created using Ultraviolet (UV) mutagenesis and nitrogen ion (N+) implantation. The alkaloid production of UN32 was 2.62 times more than that of MD33. One thousand twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…MF23 participates in dendrobine biosynthesis by regulating postmodification enzyme (cytochrome P450, aminotransferase and methyltransferase) gene expression. , Sarsaiya et al (2020) reported that D. nobile endophytic fungus T. longibrachiatum MD33 could produce the same dendrobine as the host . They also found that the MVA pathway enzyme-coding genes (hydroxymethylglutaryl-CoA synthase, farnesyl diphosphate synthase and mevalonate kinase) might participate in sesquiterpene alkaloid metabolism in T. longibrachiatum isolated from D. nobile . Xu et al (2022) reported that the TPS and CYP450 gene families might also contribute to alkaloid biosynthesis in D. nobile .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MF23 participates in dendrobine biosynthesis by regulating postmodification enzyme (cytochrome P450, aminotransferase and methyltransferase) gene expression. , Sarsaiya et al (2020) reported that D. nobile endophytic fungus T. longibrachiatum MD33 could produce the same dendrobine as the host . They also found that the MVA pathway enzyme-coding genes (hydroxymethylglutaryl-CoA synthase, farnesyl diphosphate synthase and mevalonate kinase) might participate in sesquiterpene alkaloid metabolism in T. longibrachiatum isolated from D. nobile . Xu et al (2022) reported that the TPS and CYP450 gene families might also contribute to alkaloid biosynthesis in D. nobile .…”
Section: Discussionmentioning
confidence: 99%
“… 16 They also found that the MVA pathway enzyme-coding genes (hydroxymethylglutaryl-CoA synthase, farnesyl diphosphate synthase and mevalonate kinase) might participate in sesquiterpene alkaloid metabolism in T. longibrachiatum isolated from D. nobile . 55 Xu et al (2022) reported that the TPS and CYP450 gene families might also contribute to alkaloid biosynthesis in D. nobile . 56 Wang et al (2022) reported that two dendrobine-type sesquiterpenoid alkaloids (6-hydroxydendrobine and nobilonine) from the Dendrobium endophytic bacterium Pseudomonas protegens CHA0 were synthesized mainly through the MEP pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The Fungal Transcription Factors Database FTFD 1 contains information on 61 TF families, including bHLH, bZIP, C2H2 zinc finger, Zn2Cys6, and the zinc finger type GATA. These TFs have been identified in T. atroviride , T. virens , and T. reesei ( Qian et al, 2021 ), and are involved in amino acid and vitamin synthesis, carbon and nitrogen metabolism, meiosis, and morphogenesis ( Macpherson et al, 2006 ). Following MeJA treatment, many TFs were up-regulated, including zn-clus, SET, C3H, and GNAT.…”
Section: Discussionmentioning
confidence: 99%
“…The Fungal Transcription Factors Database FTFD 1 contains information on 61 TF families, including bHLH, bZIP, C2H2 zinc finger, Zn2Cys6, and the zinc finger type GATA. These TFs have been identified in T. atroviride, T. virens, and T. reesei (Qian et al, 2021), and…”
Section: Discussionmentioning
confidence: 99%
“…In this process, cyclase, cytochrome oxidase, methyltransferase, and aminotransferase were considered to be the key enzymes, but this requires further empirical evidence. 7,192…”
Section: Biosyntheses Of Picrotoxane Sesquiterpenoidsmentioning
confidence: 99%